2020
DOI: 10.1016/j.eclinm.2020.100288
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a two bag acetylcysteine regimen to treat paracetamol overdose (2NAC study)

Abstract: Background: Previous studies of paracetamol overdose treatment show that a 2-bag, 20-h intravenous (IV) acetylcysteine regimen decreased the incidence of non-allergic anaphylactic reactions compared to the 3bag, 21 h IV regimen, but have not examined efficacy of the 20-h 2 bag regimen. Methods: This was a multi-centre observational study of paracetamol overdose presentations treated with a 2-bag IV acetylcysteine regimen (200 mg/kg over 4 h, 100 mg/kg over 16 h) compared to a 3-bag regimen, performed from 2009… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 27 publications
0
30
0
1
Order By: Relevance
“…N-acetylcysteine is reported to facilitate scavenging of APAP derived reactive metabolites and is the only treatment for APAP overdose. (Wong et al, 2020). The mechanism of APAP metabolism associated with changes in liver is presented in Figure 1.…”
Section: Metabolism Of Acetaminophenmentioning
confidence: 99%
“…N-acetylcysteine is reported to facilitate scavenging of APAP derived reactive metabolites and is the only treatment for APAP overdose. (Wong et al, 2020). The mechanism of APAP metabolism associated with changes in liver is presented in Figure 1.…”
Section: Metabolism Of Acetaminophenmentioning
confidence: 99%
“…They proposed using these assumptions that a patient ingesting 35g (500mg/kg) of paracetamol warranted an increase in infusion rate in the third bag to 13.75 mg/kg/h. 1 The median reported dose of paracetamol ingested in large cohort studies of patients treated with NAC in the UK and Australia is around 16g (210-250mg/kg) but the rates of hepatotoxicity (defined as peak ALT>1000 IU/L) is only around 4-8%, depending on the nomogram used to determine treatment 2,3 , suggesting that the vast majority of patients ingesting >16g paracetamol fare well with the current 300 mg/kg NAC dose. Hendrickson used similar stoichiometric calculations to propose infusion rates of 12.5, 18.75 and 25 mg/kg/h for patients above the 300 mg/L, 450 mg/L and 600 mg/L nomogram lines respectively.…”
mentioning
confidence: 99%
“…1 Both are associated with less adverse reactions, and in large observational studies have been shown to have similar efficacy to the traditional regimen. 8,9 Unfortunately, paracetamol overdoses have become more problematic with increased availability of larger pack sizes (massive overdoses) and the introduction of modified release preparations in some parts of the world. It is now recognised that the dose of acetylcysteine used for decades may not be effective for these cases, so clinicians now challenge the illogical 'one size fits all' to antidote dosing for paracetamol.…”
mentioning
confidence: 99%
“…In the United Kingdom, the Scottish and Newcastle Anti‐emetic Pre‐treatment for Paracetamol Poisoning (SNAP) 12‐h regimen (100 mg/kg over 2 h followed by 200 mg/g over 10 h) is being adopted, 7 while in Australia, a two‐bag simplification (200 mg/kg over 4 h followed by 100 mg/kg over 16 h) of the three‐bag regimen is now recommended 1 . Both are associated with less adverse reactions, and in large observational studies have been shown to have similar efficacy to the traditional regimen 8,9 …”
mentioning
confidence: 99%